REER imbalances and macroeconomic adjustments: Evidence from the CEMAC zone - Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2019)
The EMU crisis holds special lessons for existing monetary unions. We assess the behavior of real effective exchange rates (REERs) of members of the Central African Economic and Monetary Community (CEMAC) zone with respect to their long-term equilibrium paths. A reduced form of the fundamental equilibrium exchange rate (FEER) model is estimated and associated misalignments. Our findings suggest that for majority of countries, macroeconomic fundamentals have the expected associations with the exchange rate fluctuations. The analysis also reveals that only the REER adjustments of Cameroon and Gabon are significant in restoring the long-term equilibrium in event of a shock. The Cameroonian economic fundamentals of terms of trade, government expenditure and openness have different long-term relations with the REER in comparison to those of other member states. There is no need for an adjustment in the level of the peg based on the present quantitative analysis of REER paths.
Keywords: F31; F33; F42; F61; O55; 330; Exchange rate; Macroeconomic impact; CEMAC zone